A V2X Access Authorization Mechanism based on Decentralized ID (DID) and Verifiable Credentials (VC) - Lim, Jiho; Oh, Hansu; Sim, Kichun; Kim, Sunyoung; Kim, Ki Hyung (International Conference on Information Networking, 2023)
In this paper, we propose DID/VC-based V2X Access Authorization Mechanism that improves the CA-centered structure problem of the V2X security authentication system developed to ensure the anonymity of V2X users and create a safe operating basis for ITS. The CA-centered PKI structure represents a structure in which there is a CA that can lead or control the identity of the identity subject. In this structure, the identity subject's personal information and certificate can be stolen by a Misbehavior CA, and there is a risk of external attack such as MITM attack. Building trust in V2X networks is a major problem because it is difficult to evaluate reliability between vehicles and infrastructure in an untrustworthy environment. In this paper, we propose a DID/VC-based V2X Access Authorization Mechanism that selects a trusted authority to improve reliability, guarantees data sovereignty and privacy protection of identity subjects, and generates safe digital credentials.
Keywords: Authentication systems; Block-chain; Credential-based; Decentralised; Decentralized ID; Mechanism-based; SCMS; Security authentication; V2X; Verifiable credential; Authorization; Blockchain; DID; SCMS; V2X; VC